Minimal epitope for Mannitou IgM on paucimannose-carrying glycoproteins. (28th April 2021) - Robakiewicz, Stefania; Bridot, Clarisse; Serna, Sonia; Gimeno, Ana; Echeverria, Begoña; Delgado, Sandra; de Ruyck, Jérôme; Semwal, Shubham; Charro, Diego; Dansercoer, Ann; Verstraete, Kenneth; Azkargorta, Mikel; et al.
Abstract: Paucimannosidic glycans are restricted to the core structure [Man1–3 GlcNAc2 Fuc0–1 ] of N -glycans and are rarely found in mammalian tissues. Yet, especially [Man2-3 GlcNAc2 Fuc1 ] have been found significantly upregulated in tumors, including in colorectal and liver cancer. Mannitou IgM is a murine monoclonal antibody that was previously shown to recognize Man3 GlcNAc2 with an almost exclusive selectivity. Here, we have sought the definition of the minimal glycan epitope of Mannitou IgM, initiated by screening on a newly designed paucimannosidic glycan microarray; among the best binders were Man3 GlcNAc2 and its α1, 6 core-fucosylated variant, Man3 GlcNAc2 Fuc1 . Unexpectedly and in contrast to earlier findings, Man5 GlcNAc2 -type structures bind equally well and a large tolerance was observed for substitutions on the α1, 6 arm. It was confirmed that any substitution on the single α1, 3-linked mannose completely abolishes binding. Surface plasmon resonance for kinetic measurements of Mannitou IgM binding, either directly on the glycans or as presented on omega-1 and kappa-5 soluble egg antigens from the helminth parasite Schistosoma mansoni, showed submicromolar affinities. To characterize the epitope in greater and atomic detail, saturation transfer difference nuclear magnetic resonance spectroscopy was performed with the Mannitou antigen-binding fragment. The STD-NMR data demonstrated the strongest interactions with the aliphatic protons H1 and H2 of the α1–3-linked mannose and weaker imprints on its H3, H4 and H5 protons. In conclusion, Mannitou IgM binding requires a nonsubstituted α1, 3-linked mannose branch of paucimannose also on proteins, making it a highly specific tool for the distinction of concurrent human tumor-associated carbohydrate antigens.